A Single Surgeon's Experience With Transgender Female-to-Male Chest Surgery. Issue 3 (September 2018) - Whitehead, David M.; Weiss, Paul R.; Podolsky, Dina
Abstract : Background: Chest wall recontouring is a common surgical treatment of gender dysphoria in transmen and nonbinary individuals assigned female at birth. This study reviews more than 20 years of cases to identify risk factors for postoperative complications and likelihood of preservation of nipple sensation. Methods: One hundred thirty-seven cases of female-to-male chest wall recontouring by a single surgeon from 1994 to 2016 were reviewed, 99 of which were included for final analysis. Double-incision free nipple graft and double incision with nipple transposition on a pedicle were the most common techniques used. Complication rates between these 2 techniques were compared, and multivariate analysis was used to identify possible predictors of major complications, and minor complications. Results: No significant risk factors for major complications were identified. With regard to minor complications, advanced patient age (odds ratio [OR], 1.67; P = 0.03) and early surgical experience (OR, 5.08; P = 0.001) were found to be associated with increased risk. Preoperative hormonal treatment was found to trend toward a protective effect (OR, 0.13; P = 0.07). Conclusions: Any of the reviewed techniques are safe in practice; however, there is a learning curve associated with their use, and longer follow-up will allow for the identification of late complications. The double incision with nipple transposition on a pedicle technique can be considered for patients for whom depigmentation of the nipple-areola complex is a significant concern, especially if they are willing to tolerate a potentially suboptimal chest contour.